1998
DOI: 10.4269/ajtmh.1998.58.786
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory evaluation of a dot-blot enzyme immunoassay for serologic confirmation of illness due to Rickettsia conorii.

Abstract: Abstract. Of the 169 United States Army soldiers who deployed on a field training exercise to a remote area of Botswana for two weeks in January 1992, more than 30% developed a febrile illness within five days of their return. A diagnosis of South African tick typhus was suggested by soldiers' exposure to ticks, as well as the presence of eschars and vesicles at the site of tick bites, and tender regional lymphadenopathies. This high attack rate, experienced during such a short exposure period, emphasizes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Although blood is a complex biofluid populated with highly abundant carrier proteins, 58 that does not lend itself to straightforward biomarker discovery approaches, targeted proteomics in blood yield clinically useful diagnostics because this fluid is readily accessible. 15,59 Herein, we demonstrate translating discovery proteins to targeted proteomics using parallel reaction monitoring techniques. Although PRMs improve the sensitivity of protein detection, significant increases in sensitivity of detection can be achieved using a preenrichment step.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although blood is a complex biofluid populated with highly abundant carrier proteins, 58 that does not lend itself to straightforward biomarker discovery approaches, targeted proteomics in blood yield clinically useful diagnostics because this fluid is readily accessible. 15,59 Herein, we demonstrate translating discovery proteins to targeted proteomics using parallel reaction monitoring techniques. Although PRMs improve the sensitivity of protein detection, significant increases in sensitivity of detection can be achieved using a preenrichment step.…”
Section: Discussionmentioning
confidence: 99%
“…2 The reference standard for diagnosis of rickettsial diseases is a fourfold increase in antibody titer by the indirect immunofluorescence antibody assay using paired serum samples 2 to 4 weeks after onset of illness. 15 Patients usually do not have diagnostic serum antibody titers during the first week of illness, and a negative result by immunofluorescence antibody does not exclude the diagnosis. Therefore, many cases are initially misdiagnosed, accounting for adverse outcomes, 16 and consequently, the epidemiology of the disease is underreported.…”
mentioning
confidence: 99%
“…MSF is diagnosed based on clinical manifestations, epidemiologic data, and laboratory evidence of recent exposure to rickettsial organisms in which both culture techniques and serologic tests are used to confirm the diagnosis; however, indirect immunofluorescence (IIF) is the most commonly used confirmatory test currently [ 5 ]. A titer of 1:64 or greater is diagnostic [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In one evaluation of that assay, CPT L. Broadhurst of WRAIR and colleagues, using samples collected consequent to a SFGR outbreak among U.S. troops deployed to Botswana, found that the dipstick test read positive in more of the probable cases (62%) than did the IgG (16%) and IgM (55%) indirect immunofluorescence assays. 95 In another study, PCR amplification of DNA to detect R. rickettsii and R. typhi in experimentally infected adult D. variabilis ticks and X. cheopis fleas was demonstrated. PCR amplification of DNA provides a rapid, sensitive, highly specific assay for detection of rickettsial infection in arthropod vectors.…”
Section: Us Military Contributionsmentioning
confidence: 95%